2010
DOI: 10.1007/s10741-010-9197-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, left ventricular hypertrophy and chronic kidney disease

Abstract: Left ventricular hypertrophy (LVH) is a cardiovascular complication highly prevalent in patients with chronic kidney disease (CKD) and end-stage renal disease. LVH in CKD patients has generally a negative prognostic value, because it represents an independent risk factor for the development of arrhythmias, sudden death, heart failure and ischemic heart disease. LVH in CKD patients is secondary to both pressure and volume overload. Pressure overload is secondary to preexisting hypertension, but also to a loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 59 publications
0
65
0
2
Order By: Relevance
“…5 an overall anemia prevalence of 47.75% and progression of anemia from 26.7% in CKD stage 3 (GFR from60 mL/min/1.73 m2) to 75.5% in CKD stage 5. However, Valderrábanoet al 19 studying 4,333 patients before dialysis in a study involving 779 participating centers in 21countries, showed a greater prevalence rate of 68% for anemia though the study used 11 gm/dL for definition of anemia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5 an overall anemia prevalence of 47.75% and progression of anemia from 26.7% in CKD stage 3 (GFR from60 mL/min/1.73 m2) to 75.5% in CKD stage 5. However, Valderrábanoet al 19 studying 4,333 patients before dialysis in a study involving 779 participating centers in 21countries, showed a greater prevalence rate of 68% for anemia though the study used 11 gm/dL for definition of anemia.…”
Section: Discussionmentioning
confidence: 96%
“…1 According to above explanation, almost 90 percent of patients with a glomerular filtration rate (GFR) short of what 25 to 30 mL / min have anemia, numerous with Hemoglobin levels below 10 g/dL. 2 Without treatment, the anemia of chronic kidney disease (CKD) cause number of physiologic abnormalities and pathological problems including decreased tissue oxygen delivery and utilization, 3 , cardiac enlargement,increased cardiac output ,angina, ventricular hypertrophy, congestive heart failure, 4,5 decreased cognition and mental acuity, menstrual issues, decreased nocturnal penile tumescene, and impaired immune achievements. 6 Normocytic normochromic anemia is most overwhelming s finding of Chronic Renal Disease patients, in additions, anemia may result in growth retardation and decreased intellectual efficiency in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…The mixtures were centrifuged and then the concentration of phosphate in the supernatant was determined by UV-vis spectroscopy at λ max = 700 nm. Similarly, the experiments were carried out to determine the optimum pH and maximum adsorption of phosphate onto Fe(II)-MMT at pH of 1,2,3,4,5,6,7,8,9, and 10 and the initial amounts were 9.9, 11.5, 13.1, 14.8, 16.4, 18.1, 19.7, 21.4, 23, and 26.3 mg, respectively. All the experimental data were repeated three times and the relative errors ranged within ±3%.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH) is highly prevalent in CKD patients [148]. In an observational study including 2410 patients form the Coronary Artery Risk Development in Young Adults (CARDIA) cohort, left ventricular mass index was higher in patients with lower eGFRcys even after adjusting for potential confounders [149].…”
Section: Cardiovascular Diseases In Ckdmentioning
confidence: 99%